2009
DOI: 10.1021/ic900696f
|View full text |Cite
|
Sign up to set email alerts
|

Cerium(III), Europium(III), and Ytterbium(III) Complexes with Alcohol Donor Groups as Chemical Exchange Saturation Transfer Agents for MRI

Abstract: Lanthanide(III) complexes of macrocycles 1,4,7,10-tetrakis(2-hydroxyethyl)-1,4,7,10-tetraazacyclododecane (THED) and (1S,4S,7S,10S)-1,4,7,10-tetrakis(2-hydroxypropyl)-1,4,7,10-tetraazacyclododecane (S-THP) were studied as chemical exchange saturation transfer (CEST) agents for magnetic resonance imaging (MRI) applications. The four hyperfine-shifted alcohol protons of these Ln(III) complexes gave rise to a single 1H resonance in wet d3-acetonitrile that was separated from the bulk water resonance (Δω) by 8 ppm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 35 publications
5
42
0
Order By: Relevance
“…The only other example with four of the same donor group is found in the [Ln(STHP)] 3+ complexes that have four alcohol pendent groups (Ln III = Ce III , Eu III and Yb III ) [31, 8385]. Unfortunately, the CEST peaks of these agents are not highly shifted and the complex with the most highly shifted CEST peak, [Yb(STHP)] 3+ , produces CEST only at acidic pH values.…”
Section: Paracest Agents: Lniii Complexesmentioning
confidence: 99%
“…The only other example with four of the same donor group is found in the [Ln(STHP)] 3+ complexes that have four alcohol pendent groups (Ln III = Ce III , Eu III and Yb III ) [31, 8385]. Unfortunately, the CEST peaks of these agents are not highly shifted and the complex with the most highly shifted CEST peak, [Yb(STHP)] 3+ , produces CEST only at acidic pH values.…”
Section: Paracest Agents: Lniii Complexesmentioning
confidence: 99%
“…Naturally, this cannot be achieved on the sp 2 carboxylic carbon, but it becomes possible on a carbinolic derivative, THP (THP = 1,4,7,10-tetrakis(2-hydroxypropyl)-1,4,7,10-tetraazacyclododecane), depicted in Figure 7. [37][38][39][40][41] Following a procedure similar to what outlined for DOTMA in Figure 5, we can predict that the (SSSS)-configuration of the ligand will lead to D coordination, as shown in Figure 7.…”
Section: Chirality On the Side Armmentioning
confidence: 99%
“…[39,40] One can tentatively extend these findings to the whole Ln THP series, on account of the similar behaviour of the paramagnetic shifts recently reported for the Ce, Nd, Eu derivatives. [41] Chirality has been introduced at an even more remote position, outside the first coordination sphere, by derivatizing the carboxyl group with a chiral amine, as occurs for example with the amide DOTAMNp (Scheme 2). [42][43][44][45] It may appear surprising that in spite of the distance between the chiral centre and the DOTA scaffold, Yb DOTAMNp is completely rigid and does not show any dynamic process, in a wide range of solvents [methanol, dimethyl sulfoxide (DMSO), acetonitrile].…”
Section: Chirality On the Side Armmentioning
confidence: 99%
“…Since their sidearms had alcohol protons chemically exchangeable with bulk water, the Eu 3+ complex showed PARACEST signals at pH 6.5. 45 They further demonstrated that effective binding of 19-Eu 3+ with anions such as citrate and acetate shifted the PARACEST signals downfield, demonstrating its utility as an anion responsive probe. 46 The effect of pH on the water exchange process and relaxivity was investigated with lanthanide complexes with a series of DOTA-tetraamide ligands.…”
Section: Molecular Recognition By Cyclen-metal Complexesmentioning
confidence: 99%